Enhancement of the hydrogen productivity in microbial water gas shift reaction by Thermococcus onnurineus NA1 using a pressurized bioreactor. (9th November 2017) - Kim, Min-Sik; Fitriana, Hana Nur; Kim, Tae Wan; Kang, Sung Gyun; Jeon, Sang Goo; Chung, Soo Hyun; Park, Gwon Woo; Na, Jeong-Geol
Abstract: Here, we developed a pressurized bioreactor system that increase carbon monoxide (CO) transfer efficiency in order to enhance the hydrogen productivity in the microbial water gas shift reaction by Thermococcus onnurineus NA1. The effects of CO pressure on the hydrogen production rate, CO consumption rate and the cell growth were investigated using small scale stainless steel bottles at various CO partial pressures. It was found that CO solubility increased by applying pressure can affect hydrogen production positively as long as the increased toxicity of CO is endurable to cells. The hydrogen productivity increased to some extent with CO pressure, but decreased drastically at the pressure higher than 4 bar. On the other hand, the effect of pressure itself on the cell's activity was not as significant as that of CO solubility increase. In the experiments at various system pressures with identical CO partial pressure of 1 bar, more than 80% of the cell activity remains even at total pressure of 10 bar. Also, it was important to determine the appropriate time to increase pressure for preventing excess CO in the reactor. Based on these results, a fermentation strategy for the pressurized system was designed and applied to a 5 L bioreactor with the continuous supply of the gas containing 60% CO. When the pressure was introduced to the bioreactor up to 4 bar at CO limitation condition, the unprecedented high productivity (360 mmol L −1 h −1 ) could be obtained. Highlights: CO gas solubility increased by pressurizing can be beneficial to H2 production. The impact of pressure per se was marginal. CO toxicity impacts were reduced by applying pressure at mass transfer limitation condition. When the pressure was introduced to the bioreactor, the unprecedented high productivity could be obtained.